2019 IEEE 32nd Computer Security Foundations Symposium (CSF) 2019
DOI: 10.1109/csf.2019.00025
|View full text |Cite
|
Sign up to set email alerts
|

Journey Beyond Full Abstraction: Exploring Robust Property Preservation for Secure Compilation

Abstract: Good programming languages provide helpful abstractions for writing secure code, but the security properties of the source language are generally not preserved when compiling a program and linking it with adversarial code in a low-level target language (e.g., a library or a legacy application). Linked target code that is compromised or malicious may, for instance, read and write the compiled program's data and code, jump to arbitrary memory locations, or smash the stack, blatantly violating any source-level ab… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
92
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 44 publications
(94 citation statements)
references
References 94 publications
(276 reference statements)
0
92
0
Order By: Relevance
“…The statement of SC = can therefore be read as "whenever W↓ violates a safety property, then W does". By contraposition it has been shown that this is equivalent to the preservation of arbitrary safety properties [2]:…”
Section: Preserving Safety Propertiesmentioning
confidence: 99%
See 3 more Smart Citations
“…The statement of SC = can therefore be read as "whenever W↓ violates a safety property, then W does". By contraposition it has been shown that this is equivalent to the preservation of arbitrary safety properties [2]:…”
Section: Preserving Safety Propertiesmentioning
confidence: 99%
“…To account for this scenario, Abate et al [2] describe a class of secure compilation criteria based on the preservation of classes of properties against arbitrary target context. For each of these criteria, they give an equivalent "property-free" criterion, in the same manner as the duality between TP and CC.…”
Section: Trace-relating Secure Compilationmentioning
confidence: 99%
See 2 more Smart Citations
“…Generalizing unary properties, which describe single program runs, relational properties describe relations between multiple runs of one or more programs [Abate et al 2019;Clarkson and Schneider 2010]. Formally verifying relational properties has a broad range of practical applications.…”
Section: Introductionmentioning
confidence: 99%